2013
DOI: 10.1039/c3an00928a
|View full text |Cite
|
Sign up to set email alerts
|

A pyrene-based simple but highly selective fluorescence sensor for Cu2+ ions via a static excimer mechanism

Abstract: A pyrene-based simple fluorosensor has been synthesized by a one step process. It exhibited high selectivity towards Cu(2+) ions via fluorescence enhancement of monomer and excimer emission. The origin of excimer formation was examined and established to be of static in nature from the study of absorption and excitation spectra. The observed monomer and excimer emission in the presence and absence of Cu(2+) ion with varying pH was studied and provided probable justification. The effect of varying portions of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…Excimer emissions are characteristically observed with a broad fluorescence band with the maxima at lower energy in comparison to monomer emissions, and this band can be taken into account to examine the molecular recognition process in more detail. [35][36][37][38] Although hostdirected intramolecular excimer formation in anthracenecontaining compounds as a result π-π interactions between the anthracene units is well documented, [39][40][41] there are a few examples which form intermolecular excimer species. 42,43 Considering such unique physical properties of anthracene, we have designed a simple but highly effective methyl anthracenylimine benzoate (MAB) derivative, which has the ability to form self-assembled anthracenyl excimer species with a specific metal ion.…”
mentioning
confidence: 99%
“…Excimer emissions are characteristically observed with a broad fluorescence band with the maxima at lower energy in comparison to monomer emissions, and this band can be taken into account to examine the molecular recognition process in more detail. [35][36][37][38] Although hostdirected intramolecular excimer formation in anthracenecontaining compounds as a result π-π interactions between the anthracene units is well documented, [39][40][41] there are a few examples which form intermolecular excimer species. 42,43 Considering such unique physical properties of anthracene, we have designed a simple but highly effective methyl anthracenylimine benzoate (MAB) derivative, which has the ability to form self-assembled anthracenyl excimer species with a specific metal ion.…”
mentioning
confidence: 99%
“…Due to the important roles of copper ions in industrial, environmental, and biological processes, it is on the main daily monitoring list of civil water all the time. So, there is a great demand for the development of simple, selective, and sensitive methods for copper ions [3]. Currently there are different methods that have been developed for the detection of copper ions [4–7].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation indicated that the compound exhibits quickly obvious UV-vis absorption, color change and fluorescence response to cyanide and copper ions in acetonitrile conditions. The bonding mechanism based on spectra change and in situ 1 H NMR suggested that cyanide is bonded to 4-position of coumarin and 1:2 complexation between compound and copper ion forms.For the past few years, due to the important roles in biological, industrial and environmental processes of cyanide and copper ions, the study of optical chemosensors for cyanide [1-10] and copper ions [11][12][13][14][15][16] has attracted more and more attention of many chemists. As we all know, cyanide is a highly toxic compound and the lethal to human is minimal [17].…”
mentioning
confidence: 99%
“…For the past few years, due to the important roles in biological, industrial and environmental processes of cyanide and copper ions, the study of optical chemosensors for cyanide [1][2][3][4][5][6][7][8][9][10] and copper ions [11][12][13][14][15][16] has attracted more and more attention of many chemists. As we all know, cyanide is a highly toxic compound and the lethal to human is minimal [17].…”
mentioning
confidence: 99%